ҚАРАҚАЛПАҚ ХАЛЫҚ «АШЫҚЛЫҚ» ДӘСТАНЛАРЫНЫӉ АТҚАРЫЛЫЎЫ ҲӘМ САҚЛАНЫП ҚАЛЫЎЫНДА ХАЛЫҚ БАҚСЫЛАРЫНЫӉ ТУТҚАН ОРНЫ - Есебаев, М.М. (FAN va JAMIYAT, 2023)
The article mentions the services of Bakhshis, performers of Karakalpak folk epics, in preserving examples of folk oral creativity. Also, the work done by gardeners in this regard was analyzed separately.